2021
DOI: 10.1002/ardp.202000468
|View full text |Cite
|
Sign up to set email alerts
|

Multitarget‐directed therapeutics: (Urea/thiourea)2 derivatives of diverse heterocyclic‐Lys conjugates

Abstract: The synthesis of a new small library of molecules containing bis‐urea/thiourea pendants in lysine conjugated to three different heterocycles is described. The heterocycles used in this study have benzisoxazole/piperazine/piperidine units. After a detailed antimicrobial, antioxidant, and anti‐inflammatory evaluation, it was found that the most active compounds are 10, 11, 14, 15, 18, 19 and 10, 11, 19 and 8, 9, 12, 13, 16, 17, respectively. Further, it was observed that the presence of all three entities, that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Our results are in good agreement with data reported in the literature on the high antioxidant potential of the thiourea unit and its potential applicability in multitarget molecules by imparting antioxidant properties to them [ 95 , 96 ]. Recent studies also show that thiourea derivatives have an excellent ability to capture free radicals and act as antioxidants, as evidenced by their powerful scavenging of superoxide radical anions (O 2 •– ) and hydroxyl radicals (OH • ) [ 97 , 98 , 99 ].…”
Section: Resultssupporting
confidence: 92%
“…Our results are in good agreement with data reported in the literature on the high antioxidant potential of the thiourea unit and its potential applicability in multitarget molecules by imparting antioxidant properties to them [ 95 , 96 ]. Recent studies also show that thiourea derivatives have an excellent ability to capture free radicals and act as antioxidants, as evidenced by their powerful scavenging of superoxide radical anions (O 2 •– ) and hydroxyl radicals (OH • ) [ 97 , 98 , 99 ].…”
Section: Resultssupporting
confidence: 92%
“…The molecular docking studies were performed on the active site of 2VF5 protein, which revealed that certain conjugates interacted with proteins by π-π stacking and hydrogen bonding which also possessed good binding potency between enzyme and the ligand. Finally, the authors concluded that the existence of (thiourea/urea) 2 induced the enhanced activity, specifically the conjugates substituted by 4-F and 4-Ome as they offered the most potent results [ 185 ].…”
Section: Conjugated or Hybrid Moleculesmentioning
confidence: 99%